Essentials of Economics / 330.21 - Tucker, Irvin B. (South-Western Cengage Learning Mason, OH, 2008)
focuses on the most basic tools and topics in economics in the context of real-world issues--enabling students to see how economics impacts their own world. Now in a vibrant four-color format, ESSENTIALS OF ECONOMICS is renowned for its engaging presentation, emphasis on critical thinking, active learning environment, highly motivational pedagogy, unrivaled visual learning support, and numerous in-chapter applications and review opportunities. Its focused learning system is ideal for a course at this level. Tucker implements teaching tools and methodologies that drive the student learning process and development of critical analysis skills. Readable, sensible, and interesting, it delivers the most comprehensive and pedagogically rich treatment of introduction to economics available
Keywords: Economics